Gross Anatomy Of Radius And Ulna In Royal Bengal Tiger (Panthera Tigris) (Applied Biological Research, 2018)
Present study was carried out on the radius and ulna bones of five adult  royal Bengal tiger skeleton to notice the characteristic features from other carnivores. The radius was slightly twisted bone with an antero-posteriorly  flattened shaft and two extremities. The bicipital tuberosity was present on  the proximal part posterior surface. On the distal aspect of posterior surface  eight faint oblique lines were present. Proximal extremity had concave facet  circumscribed by a bony rim which was sharp and prominent on its lateral  part and blunt towards the medial side. Distal extremity was expanded and  was about twice the size of proximal extremity. It had a large concave facet  that extended medially and ventrally. Ulna was longer than the radius and  was fattened medio-laterally. Proximal extremity had olecranon process,  anconeus process and facet for humerus. Olecranon process possessed three  tubercles. The caudal one was largest (trifid) and lateral tubercle was  prominent and smooth and placed cranial to the medial one. Distal extremity was much smaller than the proximal extremity and had rounded facet  towards the medial side which articulated with the distal extremity of radius.  During morphometry of radius and ulna bones, a non-significant difference  was noticed between the bones of two fore limbs which may be of  biomechanical importance.
Keywords: Biomechanics; osteology; radius; tiger; ulna